Pengaruh Kualitas Pelayanan, Brand Image, Brand Awareness dan Lokasi Penjualan terhadap keputusan Pembelian Mobil Suzuki Baleno pada Pt Sejahtera Buana Trada - Teodora Septiana; Karnawi Kamar; Winanti Winanti; Dedi Dedi (Journal of Management and Creative Business, 2026)
This study aims to examine the effects of service quality, brand image, brand awareness, and sales location on the purchase decision of the Suzuki Baleno at PT Sejahtera Buana Trada. The research is motivated by Suzuki Baleno's success in leading Indonesia's hatchback market despite intensifying competition in the automotive industry and shifting consumer preferences toward more efficient vehicles. A quantitative approach with an explanatory survey method was employed. The study involved 105 Suzuki Baleno consumers selected using purposive sampling. Primary data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using multiple linear regression with SPSS software. The findings reveal that service quality, brand image, brand awareness, and sales location each have a positive and significant effect on purchase decisions. Among these variables, service quality exerts the strongest influence on consumers' purchasing decisions. Simultaneously, the four independent variables significantly affect purchase decisions, as indicated by an F-value of 6.846 with a significance level of 0.000. The coefficient of determination shows that the proposed model explains 21.5% of the variance in purchase decisions, while the remaining 78.5% is influenced by other factors beyond the scope of this study. These findings suggest that improving service quality, strengthening brand image, increasing brand awareness, and maintaining strategically located dealerships are essential marketing strategies for enhancing consumer purchase decisions in the Indonesian automotive industry.